SECURITY PROBLEM OF COMMUNICATION IN CORBA SYSTEM - Byrski, Jedrzej (Computer Science, 2020)
CORBA standard defines the mechanisms o f shearing services. The key rule plays ORB (Object Reąuest Broker) which enables location o f suitable serwer and transparent com- munication between client and serwer. This paper presents problems connected with security during communication between ORB systems. In the CORBA system the objects are identified by IOR (Interoperable Object Reference). For TCP/IP it contains IP serwer address, port and object key. Filtration may use such information as: type o f communicate, IP address o f client, object key to which client wants to access, type o f operation, clients principal. In proposed implementation thefirewall works as CORBA serwer and cooperates with half- bridge. It is registered in ORB system and provides the controlling functions fo r entering packages by IDL interface. In the paper also the structure o ffiltering module is presented. Its main part is ACL (Access Control List) with rules o f access. The performance evaluation results are also presented.